Armed Groups and the DoD Manual: Shining a Light on Overlooked Issues - Fortin, K.M.A. (Cambridge University Press, 2019)
This chapter focuses on how the DoD Manual addressses the place of armed groups in the legal framework. In doing so, the chapter focuses on four issues not analysed elsewhere in the manual (i) how the manaual conceives armed groups to be addressees of international norms (ii) how the notion of 'honour' translates into norms binding upon armed groups (iii) concepts of membership and (iv) the compellability of captured former insurgents in special operations.
Keywords: armed groups; honour; sources of law; compellability; countergangs; membership; Taverne